Assessing the sustainability of traditional agroforestry practices: a case of Mamar agroforestry in Kupang-Indonesia - Ngaji, Alfred Umbu Kuala; Baiquni, Muhammad; Suryatmojo, Hatma; Haryono, Eko (Forest and Society, 2021)
A traditional agroforestry of West Timor, namely Mamar, produces important ecosystem services to the people of this arid region, however, its management tends to change, thereby disrupting its sustainability. This study aims to assess the sustainability of Mamar agroforestry by analyzing the livelihood assests of the community, the biophysical land performance of the soil, and the value of ecosystem services. Furthermore, data, on perception and livelihood assets; the level of soil damage, the importance value index, and diversity index, the value of ecosystem services based on the opinion of experts and community leaders, as well as change in land use were collected in five villages in Kupang district using surveys with a qualitative and quantitative approach. The results showed a change of perspective in Mamar's management; the decrease in the important value index of cultural crops, the diversity index is classified as declining, there is soil damage in several parameters, and the value of ecosystem services does not focus on cultural services. Considering this result, there is a socio-ecological trade-off that reduces support for the sustainability of  Mamar as traditional agroforestry that emphasizes socio-cultural functions.